Matematika Menyenangkan dengan Team Games Tournament pada Siswa Kelas Awal - Hidayati, Laila; Lusyana, Evvy (Borneo Journal of Primary Education, 2025)
Many young children struggle with math basics when lessons focus too much on the teacher talking. This research set out to see if a more playful, hands-on approach could change that. We studied the impact of the Team Games Tournament (TGT) method, which uses games and tangible objects, to make learning math more joyful and effective for young learners. Working with a class of 24 first-graders at SD Muhammadiyah Ngawi, we observed their activities, talked with them, and used simple tests. The change was clear: the classroom came alive with energy as the children became excited and actively involved in their math lessons. The most telling result was in their test scores: the number of students who understood the material jumped from just 3 to 9. This shows us that TGT can truly create a vibrant and relatable learning space where children thrive. Our key takeaway is that while this method is powerful, some children still need extra, personalized support. Therefore, the real success lies in pairing engaging methods like TGT with dedicated one-on-one help for those who need it.